2011
DOI: 10.1007/s11999-011-1885-z
|View full text |Cite
|
Sign up to set email alerts
|

Defining Racial and Ethnic Disparities in THA and TKA

Abstract: Racial and ethnic THA and TKA utilization disparities exist. These disparities are not explained by lower disease prevalence. The existing data suggest patient education, improved health literacy regarding THA and TKA, and a patient-provider relationship leading to improved trust would be beneficial. Research providing a better understanding of the root causes of these disparities is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Others have reported minorities have less access to TKA [52,58]. Lower utilization of TKA by patients with fewer resources has also been reported [24,27]. Dunlop et al [17], on the other hand, reported, although there were lower rates of TKA among minority patients, this pattern was not seen in those younger than 65 years, which was the age of our patient population.…”
Section: Discussionsupporting
confidence: 51%
“…Others have reported minorities have less access to TKA [52,58]. Lower utilization of TKA by patients with fewer resources has also been reported [24,27]. Dunlop et al [17], on the other hand, reported, although there were lower rates of TKA among minority patients, this pattern was not seen in those younger than 65 years, which was the age of our patient population.…”
Section: Discussionsupporting
confidence: 51%
“…6,10,11,12 Of note, most prior studies have focused on the field of joint arthroplasty 10,11,12 and comparatively little work has been conducted with respect to the effect of race, ethnicity, or socioeconomic status on outcomes, morbidity, or mortality following elective spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…For elective cases such total knee arthroplasty (TKA), studies have noted that there may be cultural barriers to African- American patients undergoing TKA [37][38][39]. However, symptoms associated with CES are severe and result in patients seeking out care.…”
Section: Discussionmentioning
confidence: 99%